Prioritizing Digital Market Development for an Herbal Beverage SME: An Integrated SWOT-AHP Case Study in Indonesia - Oktaviana Rizka Amalia (CV. SPDFHarmony, 2026)
Background: Small and medium-sized enterprises must allocate scarce resources across promotion, channel development, and product refinement while protecting the operational capability needed to fulfil demand. Aim: This study prioritizes market-development strategies for Monascho, a herbal beverage SME in Jember, Indonesia, through an integrated SWOT-AHP case analysis. Methods: A descriptive single-case design used interviews, open and structured questionnaires, and documentary evidence from four firm-side informants; two marketing academics supplied AHP pairwise judgments. IFE, EFE, IE, SWOT, and AHP were applied sequentially, and the reported numerical outputs were interpreted conservatively because the archived study did not retain final AHP consistency ratios or a fully auditable factor-level calculation trail. Results: The firm recorded IFE = 2.566 and EFE = 2.631, placing it in IE Cell V. Preservative-free positioning was the leading strength, ineffective promotion the principal weakness, consumer loyalty the leading opportunity, and competition the key threat. Digital and electronic-media promotion ranked first (0.230), followed by market-reach expansion (0.190) and product innovation with packaging improvement (0.124). Conclusion: The case supports a staged sequence in which the firm first develops measurable digital demand generation, then pilots market access through qualified partners, and subsequently refines products using customer and fulfilment evidence. The findings offer context-specific decision support rather than causal estimates of performance effects